Impact of Multidisciplinary Team on Duodenoscope Reprocessing to Minimize Infections with High-Risk Organisms. (4th October 2017) - Mosier, Evan; Marasigan, Preciosa; Hall, Stephanie; Nanda, Neha
Abstract: Background: Duodenoscopes used for ERCP and EUS have complex designs, making reprocessing challenging. Media reports of high-concern organisms such as Carbapenem-resistant Enterobacteriaceae (CRE) outbreaks linked to duodenoscopes heightened awareness about reprocessing. Infections have been linked to the cleaning of the scope, its forceps elevator, use of unsterile water and the storage of scopes. Difficulty in preventing infections associated with duodenoscopes may be due to lack of communication between multiple departments involved in the process. Creation of a Multi-disciplinary Team (MDT) with clear roles, responsibilities was studied to determine its impact on the process of duodenoscope disinfection. Methods: Reprocessing of Olympus TJF-Q180V duodenoscopes was studied at a tertiary academic medical center (401 beds). Surveillance cultures of the duodenoscope tip (including forceps elevator) were evaluated from May 2016 to April 2017. A MDT was created in July 2016. The MDT comprised of Gastroenterology, Sterile processing, Infection Prevention, and Hospital Leadership. RACI Chart was used to outline roles and responsibilities for the team members when there was a positive culture from a duodenoscope after reprocessing. When a positive culture was identified, MDT determined the source of bacteria during reprocessing workflow. Based on the findings of a root cause analysis, an action plan was agreed upon. Low-concern bacteria (LCB) include Coagulase Negative Staphylococcus, Micrococci, Diptheroids and Bacillus . High-concern (HCB) bacteria include Staphylococcus Aureus, Streptococcus Viridians, Enterococcus spp . and enteric Gram-negative rods. Results: Prior to creation of the MDT, the percent of duodenoscope surveillance cultures ( n = 17) with LCB was 23.5% ( n = 4) and HCB was 29.4% ( n = 5). After implementing MDT, cultures ( n = 83), with LCB decreased to 4.82% ( n = 4) and HCB decreased to 4.82% ( n = 4). Additionally for the last 4 months, we have not identified any HCB. Identified opportunities include (not limited to) improved communication, hand hygiene, improved storage of scopes and containment of respiratory secretions. Conclusion: MDTs with clear roles are instrumental in eliminating HCB during reprocessing of duodenoscopes. Disclosures: All authors: No reported disclosures.